Asbestos-related diseases and biological index of cumulative dose in shipyard workers (1996-2015) - Barbieri, Pietro Gino; Sommigliana, Anna Benedetta (La Medicina del Lavoro, 2016)
Background: Asbestos-related diseases among shipyard workers are well known in Italy but descriptive long-term studies are limited; asbestos has been extensively used but the past exposure intensity has never been estimated because data from environmental and biological monitoring are almost absent. Objectives: To describe the asbestos-related diseases (1996-2015) diagnosed among shipbuilding workers from a very important shipyard in Northern Italy, and to assess past asbestos exposure levels by cumulative dose indices, fibres and asbestos bodies. Methods: The cases of workers suffering from asbestos-related diseases diagnosed from 1996 to 2015 were collected on the occasion of some legal trials; the diagnosis, and the asbestos occupational and non-occupational exposure, were carefully evaluated.Lung samples were obtained from subjects, taking advantage of the autopsies; asbestos fibers were counted by means of a Scanning Electron Microscope, equipped with x-ray fluorescence microanalyses at 12.0000 amplification, and asbestos bodies by means of an Optical Microscope at 500 amplification. Results: 192 malignant mesotheliomas (6 in women), 196 lung cancers and 14 asbestosis (without cancer) were observed (1996-2015); autopsies were carried out on 80% of all subjects and 98% of mesotheliomas were confirmed by autopsies. Pleural plaques occurred on 90% of mesotheliomas and 87% of lung cancers; histologically mild asbestosis were diagnosed on 28% of mesotheliomas and 48% of lung cancers. In malignant mesothelioma and lung cancer cases respectively, the duration of occupational exposure was on average 24 and 23 ys, the latency time 48 and 46 ys, hiring at the shipyard before 1970 24 and 23 ys. Out of 114 lung analysis, the burden of asbestos fibres was >10 million for 33.3% of subjects and out of 99 lung analysis asbestos bodies was >10.000 for 71.7%; the average time since last exposure was 31 ys. Both asbestos fibres and asbestos bodies concentrations were significantly higher (GMR 2,5) among mesothelioma vs lung cancer.Conclusion: A relevant number of asbestos-related diseases among shipbuilding workers, mainly mesothelioma and lung cancer, exposed in shipyard until the 1980’s were identified by an active search. Thanks to several autopsies, the diagnoses of cancer are confirmed as a cause of death, and a high frequency of histological asbestosis, previously ignored,was shown. The lung burden analysis of asbestos bodies and asbestos fibres, the largest ever performed among shipbuilding workers, confirms the spread and relevance of asbestos exposure. The best estimate of past exposure intensity was provided by both biological indices.